Trade Exposure and the Decline in Collective Bargaining: Evidence from Germany - Daniel Baumgarten; Sybille Lehwald (Center for Economic Studies and ifo Institute (CESifo), 2019)
We analyze the effect of the increase in trade exposure induced by the rise of China and the transformation of Eastern Europe on collective bargaining coverage of German plants in the period 1996–2008. We exploit cross-industry variation in trade exposure and use trade flows of other high-income countries as instruments for German trade exposure. We find that increased import exposure has led to an increase in the probability of German plants leaving industry-wide bargaining agreements, accounting for about one fifth of the overall decline in the German manufacturing sector. The effect is most pronounced for small and medium-sized plants.
Keywords: F16; J51; 330; international trade; import competition; collective bargaining